Unravelling the impact of RNA methylation genetic and epigenetic machinery in the treatment of cardiomyopathy - Li Liu; Linxing Yu; Yubo Wang; Liufang Zhou; Yan Liu; Xingshou Pan; Jianjun Huang (Elsevier, 2024)
Cardiomyopathy (CM) represents a heterogeneous group of diseases primarily affecting cardiac structure and function, with genetic and epigenetic dysregulation playing a pivotal role in its pathogenesis. Emerging evidence from the burgeoning field of epitranscriptomics has brought to light the significant impact of various RNA modifications, notably N6-methyladenosine (m6A), 5-methylcytosine (m5C), N7-methylguanosine (m7G), N1-methyladenosine (m1A), 2'-O-methylation (Nm), and 6,2'-O-dimethyladenosine (m6Am), on cardiomyocyte function and the broader processes of cardiac and vascular remodelling. These modifications have been shown to influence key pathological mechanisms including mitochondrial dysfunction, oxidative stress, cardiomyocyte apoptosis, inflammation, immune response, and myocardial fibrosis. Importantly, aberrations in the RNA methylation machinery have been observed in human CM cases and animal models, highlighting the critical role of RNA methylating enzymes and their potential as therapeutic targets or biomarkers for CM. This review underscores the necessity for a deeper understanding of RNA methylation processes in the context of CM, to illuminate novel therapeutic avenues and diagnostic tools, thereby addressing a significant gap in the current management strategies for this complex disease.